Perubahan Nilai Ekivalensi Mobil Penumpang Akibat Perubahan Karakteristik Operasional Kendaraan di Jalan Kota Semarang - Yulipriyono, EPF. Eko; Purwanto, Djoko (Department of Civil Engineering, Diponegoro University, 2017)
Passenger Car Equivalent (PCE) is a conversion factor to make equal the various types of vehicles that operating on the road section into one type of vehicles i.e. passenger cars. Indonesian Highway Capacity Manual (MKJI) 1997 has set the PCE values for various types of vehicle groups either motorized. PCE values of various types of vehicles are not absolute because many factors that affect can change over time and development of automotive technology. This study aimed to find out the changes of PCE value that occurs. As for the purpose of research to determine the current number of PCE values due to the change of operational characteristics of vehicles on a highway especially for urban highways. Data analysis for the determination of PCE values used: time headway method, speed method, capacity method, and vehicle dimension method. The conclusion of this study: PCE of light vehicles (LV) = 1 still in accordance with MJKI 1997; PCE of heavy vehicles (HV) varied depending on the road types. PCE of heavy vehicles that according to MKJI 1997 is used as a median; PCE of motorcycles (MC) of MKJI 1997 need to be adjusted to 0.4 or more, particularly in the calculation of actualy traffic flow.